Pengaruh Risiko Sistematik, Konservatisme Laba, dan Corporate Social Responsibility Terhadap Earning Response Coefficient - Anis Rahayu; Titis Puspitaningrum Dewi Kartika (Jurnal Telaah dan Riset Akuntansi, 2017)
The earnings information published by the company through the annual report is the basis for the investors to make an investment decision. The investor reaction to the earnings announcement could be seen from the movement of stock prices around the publication date of the annual report. This reaction is affected by several factors, where this study aimed to analyze the effect of systematic risk, earning conservatism, and corporate social responsibility towards earning response coefficient. The subjects of this study consisted of manufacturing companies listed in Indonesia Stock Exchange in period 2013-2015 and selected by purposive sampling. The method of data analysis used was multiple linear regression. The result of this study was systematic risk didn’t have significant effect on earning response coefficient, earning conservatism didn’t have significant effect on earning response coefficient, and corporate social responsibility had negative significant effect on earning response coefficient.KEYWORDS :  earning response coefficient, systematic risk, earning conservatism, corporate social responsibility.